2016
DOI: 10.1002/bjs.10307
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hospital volume on risk-adjusted mortality following oesophagectomy in Japan

Abstract: In Japan, high-volume hospitals had lower risk-adjusted 30-day and operative mortality rates following oesophagectomy compared with low-volume hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 18 publications
3
52
0
1
Order By: Relevance
“…However, given the operative complexity of esophagectomy and the perioperative resources necessary to care for these patients, this procedure has become increasingly centralized at larger tertiary referral centers, which are more frequently represented in ACS‐NSQIP . Moreover, the rates of anastomotic leak (13.9%) and mortality (2.7%) reported here are similar to prior studies, varying anywhere from 2.96% to 21.9% and 1.0% to 11.6%, respectively . Third, the ACS‐NSQIP does not capture 100% of operative cases performed, which could result in selection bias .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, given the operative complexity of esophagectomy and the perioperative resources necessary to care for these patients, this procedure has become increasingly centralized at larger tertiary referral centers, which are more frequently represented in ACS‐NSQIP . Moreover, the rates of anastomotic leak (13.9%) and mortality (2.7%) reported here are similar to prior studies, varying anywhere from 2.96% to 21.9% and 1.0% to 11.6%, respectively . Third, the ACS‐NSQIP does not capture 100% of operative cases performed, which could result in selection bias .…”
Section: Discussionmentioning
confidence: 56%
“…Although this increase in volume was associated with a decrease in mortality, high morbidity rates remain problematic, and the Esophageal Complications Consensus Group recently reported that 59% of patients develop at least one postoperative complication . Anastomotic leaks are estimated to occur in 11.4% of patients after esophagectomy, making it the most common surgical complication, and the third most common complication overall, behind pneumonia (14.6%) and atrial dysrhythmias requiring intervention (14.5%) …”
Section: Introductionmentioning
confidence: 99%
“…In Japan, a minimum hospital volume standard is used as an eligibility criterion for designated cancer care hospitals, and as an indicator to monitor their performance . The majority of studies on the volume‐outcome relationship previously conducted in Japan focused on a single cancer site . One study reported the volume‐survival relationship for multiple sites of cancer diagnosed in 1994‐1998; hospital volume was defined by the number of patients treated .…”
Section: Introductionmentioning
confidence: 99%
“…29 The majority of studies on the volume-outcome relationship previously conducted in Japan focused on a single cancer site. 21,[30][31][32][33][34][35] One study reported the volume-survival relationship for multiple sites of cancer diagnosed in 1994-1998; hospital volume was defined by the number of patients treated. 7 Since then, Osaka has changed in terms of its population structure, medical technology and cancer control policy, and has improved its cancer registry system.…”
mentioning
confidence: 99%
“…The reported data were results obtained at limited outstanding high‐volume facilities. Moreover, Nishigori et al reported that high‐volume hospitals had lower risk‐adjusted 30‐day and operative mortality rates compared with low‐volume hospitals. Data from the Japanese nationwide web‐based database included data on outcomes not only from high‐volume, but also from low‐volume hospitals, so that data from the Japanese nationwide web‐based database may not reflect the actual reduced invasiveness of MIE .…”
Section: Minimally Invasive Esophagectomy Versus Open Esophagectomymentioning
confidence: 99%